The Macroautophagy Machinery in MHC Restricted Antigen Presentation - Münz, Christian (Frontiers in Immunology, 2021)
Autophagy-related (ATG) gene products regulate macroautophagy, LC3-associated phagocytosis (LAP) and LC3-dependent extracellular vesicle loading and secretion (LDELS). These processes also influence antigen processing for presentation on major histocompatibility complex (MHC) molecules to T cells. Here I summarize how these different pathways use the macroautophagy machinery, contribute to MHC class I and II restricted antigen presentation and influence autoimmunity, tumor immunology and immune control of infectious diseases. Targeting these different pathways should allow the regulation of intracellular and extracellular antigen presentation to T cells to modulate protective and pathological immune responses.